Exploring the Implementation of Cambridge Curriculum in Early Elementary English Education: A Case Study - Muzaedah, Muzaedah; Muamaroh, Muamaroh; Prastiwi, Yeny; Sutopo, Anam (Universitas Hamzanwadi, 2023)
This study investigates the application of the Cambridge curriculum in teaching English to young learners, focusing on how it is tailored to their specific needs. The research was conducted at a private Islamic elementary school in Surakarta, Central Java, and centered around the teaching practices of an English teacher at the school. Through structured interviews and observations, the study aimed to gain a thorough understanding of the implementation of the Cambridge curriculum in early English education. The findings show that the teacher primarily used audio-visual and translation methods for instruction. The materials utilized included both printed and electronic books from Cambridge, enhanced with digital resources like videos, Quizizz, and the Spin Wheel application. Additionally, the study explored the assessment methods used, which encompassed daily evaluations, mid-term, and final tests. The qualitative analysis of this data provides valuable insights into the effective implementation of the Cambridge curriculum in a real elementary school environment.